The Development of a Socioscientific Issues-Based Curriculum Unit for Middle School Students: Global Warming Issue - Atabey, Nejla; Topcu, Mustafa Sami (NECMETTIN ERBAKAN UNIV, 2017)
In this study, we aimed at developing. Human and Environment. unit around SSI based instruction. We followed action research methodology in development and implementation of the unit. The participants of this study were 24 seventh graders students and the instruction was extended to eight and a half weeks, taking four hours in a week. The data collection tools included the teacher's, the students' diaries, midterm exams, and video records. The SSI-based instructional framework of Presley and colleagues (2013) guided us to develop this unit for middle school. We also used the framework for analyzing student and teachers' diaries. The correct answers were scored with 1 point while wrong answers were evaluated with 0 point for mid-term exams which were multiple choice exams. Video records were evaluated in terms of SSI-based instruction observation form. Our findings showed that the framework of Presley and colleagues (2013) was useful for the development of an effective SSI-based instruction. At the end of the study a unit started with a global warming, interacting with science ideas and practices, and ended with a final activity was presented.
Keywords: Socioscientific issues; Science teaching; Development of a SSI-based unit; Middle school students